Observation of Dispersion in the Japanese Coastal Area of Released (90)Sr, (134)Cs, and (137)Cs from the Fukushima Daiichi Nuclear Power Plant to the Sea in 2013 - Tazoe, Hirofumi (Int J Environ Res Public Health, 2019)
The March 2011 earthquake and tsunami resulted in significant damage to the Fukushima Daiichi Nuclear Power Plant (FDNPP) and the subsequent release of radionuclides into the ocean. Here, we investigated the spatial distribution of strontium-90 ((90)Sr) and cesium-134/cesium-137 ((134, 137)Cs) in surface seawater of the coastal region near the FDNPP. In the coastal region, (90)Sr activity was high, from 0.89 to 29.13 mBq L(−1), with detectable FDNPP site-derived (134)Cs. This indicated that release of (90)Sr from the power plant was ongoing even in May 2013, as was that of (134)Cs and (137)Cs. (90)Sr activities measured at open ocean sites corresponded to background derived from atmospheric nuclear weapons testing fallout. The FDNPP site-derived (90)Sr/(137)Cs activity ratios in seawater were much higher than those in the direct discharge event in March 2011, in river input, and in seabed sediment; those ratios showed large variability, ranging from 0.16 to 0.64 despite a short sampling period. This FDNPP site-derived (90)Sr/(137)Cs activity ratio suggests that these radionuclides were mainly derived from stagnant water in the reactor and turbine buildings of the FDNPP, while a different source with a low (90)Sr/(137)Cs ratio could contribute to and produce the temporal variability of the (90)Sr/(137)Cs ratio in coastal water. We estimated the release rate of (90)Sr from the power plant as 9.6 ± 6.1 GBq day(−1) in May 2013 on the basis of the relationship between (90)Sr and (137)Cs activity ((90)Sr/(137)Cs = 0.66 ± 0.05) and (137)Cs release rate.